Contribuições à análise de capacidade de hospedagem em sistemas elétricos de potência - Silva, Fabrício Montes (2017)
The hosting capacity study is the determination of the maximum amount of distributed generation that can be connected at a particular bus in the electrical system before an energy quality indicator or even a network limiting parameter has its threshold value violated. Several works seek to determine the hosting capacity linked to the main variables that affect the electrical system, being: overvoltage and overcurrent or overload. More recent works still addresses other variables such as power flow and another one that is growing in importance with the increasing input of nonlinear loads in the electric system: harmonic distortion. This work brings a joint analysis of the concept of hosting capacity seeking to be placed as a first step to unify the concept around all the variables that influence it. In this dissertation, three variables are observed: overvoltage, overcurrent or overload and harmonic distortion. To exemplify the described theories, there is a case study involving a system widely known in academia, the 14 bars of the IEEE. In a first moment the variables are analyzed independently to find the hosting capacity regarding each one of those, being later unified to a single study seeking to globalize the concept. In order to contribute to the analysis of hosting capacity in terms of harmonic distortion, a graphical tool was developed that allows better visualization of the areas of hosting capacity determined by the established limits of harmonic distortion at the point of connection.